A Study on the Effect of Medication on Patient’s Quality of Life with Alcoholic Liver Disease: Research Article (Journal of Pharma Insights and Research, 2024)
Alcoholic liver disease (ALD) encompasses a spectrum of liver disorders caused by excessive alcohol consumption, ranging from fatty liver to alcoholic hepatitis, cirrhosis, and hepatocellular carcinoma. This study aimed to evaluate the effect of standard medication on patients' quality of life (QOL) with ALD and analyze health-related QOL before and after treatment. A prospective, single-centered observational study was conducted on 150 patients diagnosed with ALD at Vedantha Hospital and Government General Hospital, Guntur. Patient data, including medical history, medication history, and liver function biomarkers, were collected. The standard treatment included prednisolone, pentoxifylline, infliximab, L-ornithine L-aspartate, and silymarin. Patients' health-related QOL was assessed using the SF-36 questionnaire pre- and post-treatment. Liver function biomarkers, including total bilirubin, AST, ALT, GGT, and alkaline phosphatase, were analyzed. Post-treatment, significant improvements were observed in patient-reported QOL and liver function biomarkers. The study provides strong evidence supporting the efficacy of the medicinal intervention, demonstrated by notable enhancements in patient-reported outcomes and liver function biomarkers. Comprehensive evaluation of patient health outcomes through subjective measures like the SF-36 questionnaire and objective biomarkers offers a holistic assessment of treatment effectiveness in ALD